2008
DOI: 10.1002/jcc.21001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modeling of A1 and A2A adenosine receptors: Comparison of rhodopsin‐ and β2‐adrenergic‐based homology models through the docking studies

Abstract: Adenosine receptors (ARs) are members of the superfamily of G protein-coupled receptors. The homology models of adenosine A1 and A2A receptors were constructed. The high-resolution X-ray structure of bovine rhodopsin and crystal structure of beta2-adrenergic receptor were used as templates. The binding sites of the A1 and A2A ARs were constructed by using data obtained from mutagenesis experiments as well as docking simulations of the respective AR antagonsists DPCPX and XAC. To compare rhodopsin- and beta2-ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 107 publications
1
23
0
Order By: Relevance
“…The recently solved human A 2A AR-ZM241385 co-crystal structure revealed that the prototypical non-xanthine antagonist, ZM241385, binds very differently to the receptor than had been predicted by models based on rhodopsin binding to retinal (7,8). The long axis of ZM241385 lies orthogonal to the membrane plane and has a large number of interactions with residues in TM domains 5-7, and extracellular loops 2 and 3 (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recently solved human A 2A AR-ZM241385 co-crystal structure revealed that the prototypical non-xanthine antagonist, ZM241385, binds very differently to the receptor than had been predicted by models based on rhodopsin binding to retinal (7,8). The long axis of ZM241385 lies orthogonal to the membrane plane and has a large number of interactions with residues in TM domains 5-7, and extracellular loops 2 and 3 (3).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, we found that the binding mode of ZM241385 to its receptor is very different from the binding of ligand to other GPCRs with known crystal structures, the beta-blockers timolol, carazolol, and cyanopindolol co-crystallized with turkey ␤ 1 -adrenoreceptor or human ␤ 2 -adrenoceptors and retinal cocrystallized with bovine and squid rhodopsin, and binding of these ligands to their cognate receptors has very little overlap with ZM241385 binding to A 2A AR when all available receptor structures are superimposed (6). In addition, the orientation of ZM241385 in the binding pocket deviates greatly from that of homology models, which used the rhodopsin structure as a template (7)(8). Therefore, models for ligand-A 2A AR interac-tions based upon these other GPCR-ligand structures can give only rough picture of ligand binding (9).…”
mentioning
confidence: 99%
“…Katritch et al (155) have demonstrated such potential by b 2 -AR receptor optimization in the presence of docked ligands and the resultant improved prediction of agonist binding affinities. Generally, optimization of GPCR binding sites by flexible receptor docking, particularly as a measure to improve and test the quality of GPCR homology model, has evolved as a mainstream theme in the GPCR field as exemplified by a number of recent studies (156)(157)(158)(159).…”
Section: Gpcrs As a Case Study For Docking And Virtual Screeningmentioning
confidence: 99%
“…Further, in a recent study by Mantri and coworkers on new antagonists for the A 2A AR, it was demonstrated that tremendous substituent flexibility exists in this area of the pharmacophore (Mantri et al, 2008). This observation correlates well with the directionality of the phenylethylamine substituent in ZM241385 because it extends toward the more solvent-exposed extracellular region (ECL2 and ECL3) rather than toward the transmembrane domain of the receptor, as was previously proposed (Martinelli & Tuccinardi, 2008;Yuzlenko & Kiec-Kononowicz, 2009). …”
Section: E169 (Ecl2)mentioning
confidence: 50%
“…3A). This cannot be reconciled with earlier molecular modeling studies based on rhodopsin homology models in which ZM241385 and other antagonists were docked into a binding site emulating that of the b 2 -adrenoceptor and rhodopsin (Martinelli & Tuccinardi, 2008;Yuzlenko & Kiec-Kononowicz, 2009). Second, the organization of the extracellular loops is markedly different from those of the b 1 -adrenoceptor, the b 2 -adrenoceptor, or the bovine and squid rhodopsins.…”
Section: The Key Differencesmentioning
confidence: 61%